2014
DOI: 10.1142/s0218495814500137
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Lending Practices: Enabling South African Women Entrepreneurs to Access Start-Up Capital

Abstract: This study explores gendered lending and marketing practices of start-up capital to women entrepreneurs in South Africa. A multi-method research design, comprising of 6 in-depth interviews with experts, and a survey of 50 women entrepreneurs was adopted using convenience and snowball sampling techniques, respectively. The findings revealed that women entrepreneurs are experiencing gendered discriminatory practices embedded in lending practices used by financial institutions, thereby discouraging them to ventur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
1
16
0
2
Order By: Relevance
“…The responsible factor of low empowerment is gender discrimination. As gender discrimination is one of the problem in most of the developing countries in which men is dominants in social and economic decision making (Derera et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The responsible factor of low empowerment is gender discrimination. As gender discrimination is one of the problem in most of the developing countries in which men is dominants in social and economic decision making (Derera et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In developing and emerging nations, entrepreneurship is essential for the development and growth of the nation's economy (Derera et al, 2014;Faisal et al, 2017). Women engaged in entrepreneurship activities to generate revenue to support their families (Di Gregorio, 2013;Steel, 2017).…”
Section: Challenges and Barriersmentioning
confidence: 99%
“…Capital is crucial for entrepreneurship development and starting new endeavors (Babiker et al, 2017;Chinomona & Maziriri, 2015). Women entrepreneurs face many challenges, predominantly concerning access to finance (Babiker et al, 2017;Derera et al, 2014;Maden, 2015). Derera et al (2014) found that lenders avoid providing women with loans as perceiving women entrepreneurs lack management skills and entrepreneurial knowledge.…”
Section: Challenges and Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that male startups have a higher capitalization and a higher level of revenues compared to female startups. Derera et al (2014) explore the credit capital market aimed at female entrepreneurship through a context study carried out in South Africa with an interview of 50 female entrepreneurs. The results of the research revealed that women entrepreneurs experience gender discriminatory practices in requesting funds from financial institutions, thus discouraging them from venturing into nontraditional and riskier sectors.…”
Section: A4 Differences Between Men and Womenmentioning
confidence: 99%